Pengaruh Jumlah Penduduk, IPM, dan TPT terhadap Kemiskinan di DIY 2018–2023 - Gabriel Eksousia Oktaf; Jeane Talakua (Serat Acitya, 2025)
This study aims to analyze the influence of population size, Human Development Index (HDI), and Open Unemployment Rate (OUR) on poverty levels in regencies/cities of Special Region of Yogyakarta during 2018-2023 period. The research employed quantitative design with panel data regression analysis approach across five regencies/cities in DIY. Secondary data were obtained from official publications of Statistics Indonesia Yogyakarta Province and analyzed using Fixed Effect Model and Random Effect Model with Stata 17 software. The research findings indicate that HDI has negative and significant effect on poverty level, suggesting that improvement in human resource quality effectively reduces poverty. OUR proved to have positive and significant effect on poverty, confirming that increased unemployment raises poverty levels. Conversely, population size shows no significant influence on poverty in DIY. These findings provide strategic implications for local government to prioritize investment in education and health sectors as well as job creation programs in poverty alleviation efforts. High inter-regional heterogeneity indicates the necessity for policy approaches tailored to specific characteristics of each regency/city in DIY.